Agilicoccus flavus gen. nov., sp. nov., a novel member of the family Dermatophilaceae isolated from the Pearl River. Issue 10 (7th October 2021) - Yin, Ling-Zi; Liu, Ze-Tao; Li, Jia-Ling; Wang, Pan-Deng; Dong, Lei; Duan, Li; Luo, Xiao-Qing; Fang, Bao-Zhu; Li, Wen-Jun
Abstract : A novel actinobacterium, designated strain SYSU M44304 T, was isolated from freshwater samples in the Pearl River Estuary. The isolate was Gram-stain-positive, aerobic, coccus-shaped, oxidase-positive and motile. The cell wall contained meso -diaminopimelic acid as its diagnostic diamino acid. The predominant menaquinone was MK-8. The major polar lipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol, phosphatidylethanolamine and seven unidentified phospholipids. The major fatty acids were C16 : 0 and C16 : 1 . The G+C content based on genomic DNA was 73.2 mol %. The nearest phylogenetic neighbours to the novel strain were Mobilicoccus pelagius NBRC 104925 T and Mobilicoccus caccae YIM 101593 T . On the basis of chemotaxonomic and physiological characteristics and phylogenetic analysis, strain SYSU M44304 T should be considered to represent a novel species of a new genus in the family Dermatophilaceae, for which we propose the name Agilicoccus flavus gen. nov., sp. nov. The type strain of Agilicoccus flavus is SYSU M44304 T (=NBRC 114808 T =CGMCC 1.18608 T ).